(untitled) (Journal of the College of Basic Education, 2022)
Our research deals with the emotional alternative to music in the cinematic film, and the research problem is determined by the following question: Is music obligatory in the narrative film? And when can it be replaced as an emotional substitute? The importance of the research lies in the fact that it studies a new case in film production, which is making a film without music. This study is of interest to specialists in the field of cinematic art, scholars and connoisseurs of film art, and provides the cinematic library with a new type of study. The research dealt with three topics, namely: 1- Music in the Narrative Film, 2- Movement in the Motion Picture Film, and 3- The Emotional Alternative to Music. Then an analysis of the movie (A Separation) directed by (Asghar Farahidi).